Regional integration and export supply constraints: Evidence from ECOWAS zone - Kwami Ossadzifo Wonyra (West African Journal of Monetary and Economic Integration, 2018)
The objective of this research is to reexamine the constraints to export supply in ECOWAS countries, mainly in intra-regional trade. To achieve this objective, we use gravity model estimated with the Pseudo-Poisson Maximum Likelihood (PPML) techniques. Our results show that the number of products positively affects intra- and extra-regional exports. Moreover, the estimates show tariffs are not a constraint on ECOWAS countries' export supply. From these results, we conclude that the low export diversification of ECOWAS economies remains the major constraint on their capacity to supply the intra-regional market and the market of their main trading partners. As policy implication, ECOWAS countries have to continue to promote export diversification strategies. On the other hand, one of the challenges of these diversification policies remains the capacity of ECOWAS countries to integrate the requirements of non-tariff measures in order to respond, to a lesser extent, to international demand.
Keywords: F1; F14; F15; 330; exports supply constraints; intra-regional trade; gravity model